معالم التربية البدنية والرياضية في المراحل التعليمية الثلاث - مزروع, السعيد; زيدان, فاطمة الزهراء (دفـاتر المـــــــــــخبـر, 2018)
ملخص : تعني كلمة التربية أشياء مختلفة بالنسبة للأفراد المختلفين فالتربية هي مجموعة من الخبرات التي تمكن الفرد من فهم أشياء جديدة بطريقة أفضل ، والمهمة الأولى للتربية هي أنها تعمل على زيادة المعرفة وتنميتها والارتقاء بالفرد عن طريق تنمية مهاراته وتشجيع روح الابتكار وغرس الاتجاهات السليمة.مما يساعد على أن يحيا الفرد حياة صالحة نافعة، ولا يقتصر دور التربية على نقل وتداول المعرفة فقط ولكن الأمر يتعدى ذلك لتشير التربية الى نوعية العلاقات التي تحدث بين الأفراد .إن المرء يستطيع أن يرى بسهولة مدى أهمية الدور الذي تلعبه التربية البدنية في التربية العامة ،إذ أنها تشارك في بناء الفرد من الناحية الجسمية والانفعالية والعقلية والاجتماعية ، فالعقل والجسم يمثلان وحدة واحدة كل منهما يزود الآخر بالقوة والتربية البدنية عملية تتم بممارسة أوجه النشاط لتنمي وتصون جسم الإنسان. Summary : The term breeding different things for individuals of different education focuses on is a set of experiences that enable the individual to understand new things a better way, and the first task of breeding is that they are working to increase the knowledge and the development and upgrading of the individual through the development of skills and encourage a spirit of innovation and cultivate trends Sulaimh.mma helps to Long live the individual good life useful, is not limited to the role of education and the exchange of knowledge only move but it goes beyond that to suggest education to the quality of relationships that occur between individuals. the one can easily see how important the role of physical education in public education, as they participate in the construction of the individual in terms of physical, emotional, mental, social, and reason with the body represent one unit each provides the other by force and physical education takes place from the exercise aspects of the activity to develop and maintain the human body